Gerbrand Ban. Een aanvulling - Ekkart, R. E. O. (The Rijksmuseum Bulletin, 1992)
This article is an addition to R.E.O. Ekkart’s article in Bulletin van het Rijksmuseum 39 (1991), no. 4, pp. 426-34: Gerbrand Ban.